1985
DOI: 10.1056/nejm198505303122204
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Blood Levels in Health and Disease

Abstract: We tested HemoQuant, a quantitative assay of fecal blood based on the fluorescence of heme-derived porphyrin, in 106 healthy volunteers, 170 patients with gastrointestinal symptoms but with normal diagnostic studies, 44 patients with gastrointestinal cancer, 75 patients with benign polyps, and 374 patients with a variety of other benign gastrointestinal lesions, including ulcers and erosions. In 98 per cent of the healthy volunteers, fecal hemoglobin concentrations were less than 2 mg per gram of stool. Levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(57 citation statements)
references
References 35 publications
2
53
1
1
Order By: Relevance
“…In accordance with our results, several authors have observed that the sensitivity of the G-FOBT decreases as the amount of bleeding of the lesion increases (Morris et al, 1976;Stroehlein et al, 1976;Herzog et al, 1982;Ahlquist et al, 1985;Macrae and St John, 1987). As in other studies, in our population, the measured intensity of bleeding of invasive cancers was higher than that of high-risk adenomas (Levi et al, 2007;Ciatto et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, several authors have observed that the sensitivity of the G-FOBT decreases as the amount of bleeding of the lesion increases (Morris et al, 1976;Stroehlein et al, 1976;Herzog et al, 1982;Ahlquist et al, 1985;Macrae and St John, 1987). As in other studies, in our population, the measured intensity of bleeding of invasive cancers was higher than that of high-risk adenomas (Levi et al, 2007;Ciatto et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…An assay kit for faecal haemoglobin based upon the overall analysis of porphyrins is available (HemoQuant) (Ahlquist et al, 1985) but its capability to detect nonsteroidal induced gastrointestinal blood loss has not been evaluated. Additionally the less selective assay would make it more sensitive to artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…A further study in healthy volunteers (mean age 30 years), however, demonstrated no FOB loss detectable by guaiac-based FOB testing in individuals taking up to 325 mg daily for 30 days [16]. It is also known that FOB testing is a poor indicator of significant upper gastrointestinal pathology and previous studies suggest that it is unnecessary for patients with a positive FOB test to undergo upper gastrointestinal investigations unless they have upper gastrointestinal symptoms [17,18]. …”
Section: Discussionmentioning
confidence: 99%